THE IMPACT OF FOREIGN DEBT ON IMPLEMENTATION OF INDONESIA'S FOREIGN POLICY 2014-2022 - Asep Setiawan; Djoni Gunanto; Hamka; Muhammad Yusuf Saputra (Universitas Sulawesi Barat, 2022)
A country's foreign debt is aimed at maintaining economic growth. However, in practice, it also affects bilateral relations and international behavior. Indonesia has accumulated foreign debt reaching Rp 7000 trillion from various countries and institutions. This study aims to examine the impact of foreign debt on Indonesia's foreign policy during Joko Widodo's administration from 2014-2022. The study uses a qualitative approach, with data collected through interviews of government officials and academics as well as analysis of document sources. This research uses the concepts of foreign debt, foreign policy, and complex interdependence. The results showed three patterns of Indonesia's foreign relations with debtor countries. First, Indonesia establishes positive relationships with debtor countries. Second, Indonesia avoids getting involved in conflicts with cricket-giving countries on a number of bilateral issues. Third, Indonesia is reluctant to criticize creditors involved in bilateral and international issues while carrying out free and active foreign policy.